A critique of the principle of 'respect for autonomy', grounded in African thought. Issue 2 (3rd May 2017) - Behrens, Kevin G.
Abstract: I give an account how the principle of 'respect for autonomy' dominates the field of bioethics, and how it came to triumph over its competitors, 'respect for persons' and 'respect for free power of choice'. I argue that 'respect for autonomy' is unsatisfactory as a basic principle of bioethics because it is grounded in too individualistic a worldview, citing concerns of African theorists and other communitarians who claim that the principle fails to acknowledge the fundamental importance of understanding persons within the nexus of their communal relationships. I defend the claim that 'respect for persons' is a more appropriate principle, as it is able to acknowledge both individual decision making and the essential relationality of persons. I acknowledge that my preference for 'respect for persons' is problematic because of the important debate around the definition of 'personhood' in bioethics discourse. Relying on Thaddeus Metz's conception of moral status, I propose a relational definition of personhood that distinguishes between persons with agency and persons without agency, arguing that we have different moral obligations to these distinct categories of persons. I claim that this conception of personhood is better able to accommodate our moral intuitions than conventional approaches, and that it is able to do so without being speciesist or question‐begging.